2-(4X-17)=6(X-2)

Simple and best practice solution for 2-(4X-17)=6(X-2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2-(4X-17)=6(X-2) equation:


Simplifying
2 + -1(4X + -17) = 6(X + -2)

Reorder the terms:
2 + -1(-17 + 4X) = 6(X + -2)
2 + (-17 * -1 + 4X * -1) = 6(X + -2)
2 + (17 + -4X) = 6(X + -2)

Combine like terms: 2 + 17 = 19
19 + -4X = 6(X + -2)

Reorder the terms:
19 + -4X = 6(-2 + X)
19 + -4X = (-2 * 6 + X * 6)
19 + -4X = (-12 + 6X)

Solving
19 + -4X = -12 + 6X

Solving for variable 'X'.

Move all terms containing X to the left, all other terms to the right.

Add '-6X' to each side of the equation.
19 + -4X + -6X = -12 + 6X + -6X

Combine like terms: -4X + -6X = -10X
19 + -10X = -12 + 6X + -6X

Combine like terms: 6X + -6X = 0
19 + -10X = -12 + 0
19 + -10X = -12

Add '-19' to each side of the equation.
19 + -19 + -10X = -12 + -19

Combine like terms: 19 + -19 = 0
0 + -10X = -12 + -19
-10X = -12 + -19

Combine like terms: -12 + -19 = -31
-10X = -31

Divide each side by '-10'.
X = 3.1

Simplifying
X = 3.1

See similar equations:

| 5y^2+3y-10=0 | | -6+r=-16 | | 4+t=4 | | a+15=20 | | -24=8t(1-2t) | | (-0.4x^2-0.1x+1)=0 | | x+2*6x=3x+15 | | 10=30x^2 | | -15x+35=20 | | 25+x=-9 | | 54=-4x | | -13=x+17 | | hongki+2x=0 | | a-5=-4 | | x^2+2hx=x-h^2 | | 27(x^2-4x+4)-12=0 | | 4h^2+4x^3+4h^2x=0 | | 5x+18y-14z=12 | | 9267910643x+790x-7780=387 | | 27x^2+96=0 | | 2x+5=5x+9 | | 173x+928x=41*x | | 173x+928x=41 | | -24y^2=9y | | X-0.7=8.47 | | 4x^3-12x^2+2x+18=0 | | 30r^2=-15r | | 4x-29=-21+6x | | 5p+7-5p=-7(p-3) | | 15(5c-1)-4=73c+15 | | 3z=16-37 | | M^2+16=8m |

Equations solver categories